Deletion of the GntR8 transcriptional regulator impairs Brucella abortus intracellular survival and virulence by modulating stress response genes - Li, Shuwen; Han, Kun; Peng, Xiaowei; Wang, Nan; Ning, Wenqing; Ge, Shengxin; Xu, Lei; Ding, Jiabo; Zhang, Xinyu; Yang, Xiaowen (Frontiers in Immunology, 2025)
GntR transcription factors are emerging as critical regulators of bacterial metabolism, stress responses, and pathogenicity, however, their roles in the virulence mechanisms of Brucella abortus remain poorly understood. In this study, we generated a gntR8 (BAB_RS24500) deletion strain (ΔgntR8) in B. abortus 2308 and systematically investigated its role in virulence. The results demonstrate that deletion of gntR8 markedly impairs intracellular survival of B. abortus in RAW264.7 cells and significantly reduces virulence in a mouse infection model. Moreover, the ΔgntR8 strain exhibited increased sensitivity to oxidative stress, correlating with decreased expression of stress response genes. Integrative Dap-seq and RNA-seq analyses revealed that GntR8 directly binds to and positively regulates the clpP gene, a key component involved in oxidative stress defense. Deletion of clpP similarly resulted in diminished antioxidant capacity and intracellular survival, supporting a critical regulatory axis mediated by GntR8. Collectively, these findings provide novel insights into the molecular mechanisms by which GntR8 transcriptionally regulates oxidative stress responses and pathogenicity in B. abortus. The identification of GntR8 as a key virulence regulator highlights its potential as a therapeutic target, offering promising avenues for novel intervention strategies against brucellosis.